VALIDITY OF THE FAST SCAN FOR DIAGNOSIS OF INTRAABDOMINAL INJURY IN BLUNT ABDOMINAL TRAUMA - Iqbal, Yasmeen; Taj, Muhammad Naeem; Ahmed, Anis; Rehman, Zia Ur; Akbar, Zakia (Journal of Ayub Medical College Abbottabad, 2014)
Background: Blunt abdominal trauma is regularly encountered in the emergency department. The aim of the study is to determine the validity of assessment with sonography for trauma (FAST) scans in the evaluation of BAT in comparison to Computed tomogram/Exploratory laparotomy (CT/ELAP). Methods: This cross-sectional study was carried out at Ayub Teaching Hospital Abbottabad from January 2010 to December 2011. FAST was performed as part of the primary or secondary survey of the trauma patient in the emergency department in all patients with suspected blunt abdominal trauma. All of them also underwent either CT or ELAP depending on their clinical condition. The validity of FAST scan in comparison to CT/ELAP was documented. Results: Our study included 100 patients with suspected blunt abdominal trauma. The mean age was 31.52±16.79 years with 88% males. Road traffic accidents accounted for 80% cases and 20% were due to fall. Seventy percent were hemodynamically stable and 30% were unstable. Haemodynamically unstable patients had significantly more positive FAST scans and more positive CT/ELAP (p<0.05). Of the total, 52% had positive CT/ELAP and 54% had positive FAST scan. Majority (28%) had splenic injury. A positive scan had a statistically significant probability of a confirmed blunt abdominal trauma on CT/ELAP; p=0.00, OR=8.095, 95% CI=3.3-19.8. FAST scan had a sensitivity, specificity, positive predictive value and negative predictive value of 76.92%, 70.83%, 74.07% and 73.9% respectively. Conclusion: FAST scan had lesser accuracy as compared to previously published local and international data. More work is required before it can be routinely utilized to triage the blunt abdominal trauma patients to laparotomy. Keywords: Blunt, abdominal trauma, laparotomy, FAST, scan